2022
DOI: 10.1111/gcb.16198
|View full text |Cite
|
Sign up to set email alerts
|

Using nitrification inhibitors and deep placement to tackle the trade‐offs between NH3 and N2O emissions in global croplands

Abstract: Ammonia (NH3) and nitrous oxide (N2O) are two important air pollutants that have major impacts on climate change and biodiversity losses. Agriculture represents their largest source and effective mitigation measures of individual gases have been well studied. However, the interactions and trade‐offs between NH3 and N2O emissions remain uncertain. Here, we report the results of a two‐year field experiment in a wheat‐maize rotation in the North China Plain (NCP), a global hotspot of reactive N emissions. Our ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…The agricultural systems that promote soil carbon sequestration also stimulate nitrification and the subsequent release of nitrous oxide [528][529][530]. Nitrification inhibitors are a "double-edged sword" [15] that could promote ammonia emissions from soil [531].…”
Section: Agricultural Use Of the Recovered Biofertilizersmentioning
confidence: 99%
“…The agricultural systems that promote soil carbon sequestration also stimulate nitrification and the subsequent release of nitrous oxide [528][529][530]. Nitrification inhibitors are a "double-edged sword" [15] that could promote ammonia emissions from soil [531].…”
Section: Agricultural Use Of the Recovered Biofertilizersmentioning
confidence: 99%
“…Urease is an enzyme contributing to the breakdown of urea to ammonium, which can be readily volatilized to NH3 and so UIs contribute to the reduction of NH3 emissions. In addition to a reduction in NH3 and N2O emissions, the use of NIs and UIs lowers the degree to which N is leached to surface and ground waters, contributing to a reduction of indirect emissions [31] . UIs also improve the efficiency of urea, bringing it in line with N-fertilizers (such as ammonium nitrate), which can either improve yield due to better N use or allow for reduced N application rates.…”
Section: Use Of Nitrification and Urease Inhibitorsmentioning
confidence: 99%
“…Lower quantities of synthetic N-fertilizer applied will also cause a reduction in GHGs from fertilizer manufacturing. There is a potential for increased NH3 loss when NIs and UIs are used in combination due to the buildup of soil ammonium [31] . In addition, there are potential mitigation gains with minimal negative trade-offs with natural alternatives to chemical UIs [39] which still need to be explored.…”
Section: Potential Opportunities For Co-benefits and Trade-offs With ...mentioning
confidence: 99%
“…(3) There is a lack of analysis on the comprehensive environmental effect of one-time deep application in the field. For example, some studies found that concentrated deep application would increase the risk of nitrogen leaching and N 2 O emission loss [21,22]. It is necessary to optimize the one-time fertilization technology to reduce the total loss of nitrogen and improve its utilization efficiency.…”
Section: Implementation Obstaclesmentioning
confidence: 99%